SKF-83959 is not a highly-biased functionally selective D(1) dopamine receptor ligand with activity at phospholipase C - Lee, Sang-Min (2014)
SKF-83959 [6-chloro-7,8-dihydroxy-3-methyl-1-(3-methylphenyl)-2,3,4,5-tetrahydro-1H-3-benzazepine] is reported to be a functionally selective dopamine D(1) receptor ligand with high bias for D(1)-mediated phospholipase C (PLC) versus D(1)-coupled adenylate cyclase signaling. This signaling bias is proposed to explain behavioral activity in both rat and primate Parkinson’s disease models, and a D(1)-D(2) heterodimer has been proposed as the underlying mechanism. We have conducted an in-depth pharmacological characterization of this compound in dopamine D(1) and D(2) receptors in both rat brain and heterologous systems expressing human D(1) or D(2) receptors. Contrary to common assumptions, SKF-83959 is similar to the classical, well-characterized partial agonist SKF38393 in all systems. It is a partial agonist (not an antagonist) at adenylate cyclase in vitro and ex vivo, and is a partial agonist in D(1)-mediated β-arrestin recruitment. Contrary to earlier reports, it does not have D(1)-mediated effects on PLC signaling in heterologous systems. Because drug metabolites can also contribute, its 3-N-demethylated analog also was synthesized and tested. As expected from the known structure-activity relationships of the benzazepines, this compound also had high affinity for the D(1) receptor and somewhat higher intrinsic activity than the parent ligand, and also might contribute to in vivo effects of SKF-83959. Together, these data demonstrate that SKF-83959 is not a highly-biased functionally selective D(1) ligand, and that its reported behavioral data can be explained solely by its partial D(1) agonism in canonical signaling pathway(s). Mechanisms that have been proposed based on the purported signaling novelty of SKF-83959 at PLC should be reconsidered.